Prenatal diagnosis of well-developed fetus in fetu with spontaneous movement in a resource-limited setting: A case report - Bella Stevanny; Putri Mirani; Elsye Ruth Frida Thene; Cindy Kesty (Elsevier, 2024)
Fetus in fetu (FIF) is a rare congenital anomaly characterized by the presence of a parasitic monozygotic twin encased within the body of its host twin. Because FIF is asymptomatic throughout pregnancy, it is mainly diagnosed in children with an abdominal mass after birth. In the case reported here, at 38-39 weeks of gestation, a 33-year-old woman (gravida 4, para 3) was referred for routine obstetric ultrasonography. Fluid accumulation was identified along with calcification resembling two well-developed legs and trunk with undifferentiated organs inside. Slight spontaneous movement of the legs was observed. The fetus was delivered based on the presumed diagnosis of FIF. Postnatal sonography and computed tomography (CT) supported the diagnosis. The neonate underwent surgical excision of the tumor and was discharged on the eighth postoperative day. Ultrasound can be used to provide accurate prenatal diagnosis of FIF. Early diagnosis is important to improve outcomes.